Improvement of lung function and pulmonary hypertension after pulmonary aneurysm repair: case series. (1st February 2019) - Akagi, Satoshi; Ejiri, Kentaro; Kasahara, Shingo; Nakamura, Kazufumi; Ito, Hiroshi
Abstract : Pulmonary artery aneurysms (PAA) can be complicated with pulmonary arterial hypertension (PAH), causing sudden death due to PA rupture and dissection. Because treatment with PAH‐targeted drugs does not always prevent PAA progression, prophylactic surgical repair of the PAA seems a promising alternative. However, although it avoids rupture and dissection of the PAs, additional benefits have not been forthcoming. We therefore present two patients with co‐existing PAH and a PAA who underwent surgical repair of the aneurysm. Following the surgery, their lung function and pulmonary hypertension improved. Optimal treatment of PAA remains uncertain, however, with no clear guidelines regarding the best therapeutic approach. This case series provides physicians with reasons to repair PAA surgically in patients with PAH.